The Holy See at the Beginning of World War I - Šmíd, Marek (Historica Olomucensia, 2014)
The paper deals with the attitude of the Holy See and its representative Pope Benedict XV at the beginning of World War I. It describes concrete steps of the Roman pontiff in a dramatic period of the world conflict and analyses a content of Papal encyclicals, notes and telegrams, which he used to intervene in favour of peace at governments of states at war. His activities were numerous and rigidly strived to protect a human life, save a fellowman and alleviate suffering of all people hit by war. Even though the first reaction to the outbreak of war was a speech of Pope Pius X, his successor Benedict XV took a similar attitude shortly after his election and appealed to conscience and moral principles of all representatives of world powers. His secret as well as public missions, selfless involvement in World War I and moreover, the intervention in profit of the sick, suffering and captives give evidence that the Holy See definitely did not stay passive in the era of the biggest known conflict of the human history up to now.
Keywords: World War I; Benedict XV; the Holy See; peace efforts; 1914-1918